2003
DOI: 10.1002/chin.200339044
|View full text |Cite
|
Sign up to set email alerts
|

Pyridinium Bromochromate: A New and Efficient Reagent for Bromination of Hydroxy Aromatics.

Abstract: Halogenation Halogenation O 0235 Pyridinium Bromochromate: A New and Efficient Reagent for Bromination of Hydroxy Aromatics. -The title compound, readily prepared from HBr, pyridine and CrO3 is described as a useful reagent for the regioselective high-yielding bromination of hydroxyarenes. -(PATWARI, S. B.; BASEER, M. A.; VIBHUTE*, Y. B.; BHUSARE, S. R.; Tetrahedron Lett. 44 (2003) 26, 4893-4894; Dep. Chem., Yeshwant Mahavidyalaya, Nanded 431 602, India; Eng.) -Mais 39-044

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…In 2003, Patwari et al reported this reagent as an efficient brominating agent for the bromination of hydroxy aromatics. 1183 PBC was used to brominate various substituted hydroxyacetophenones, hydroxy aldehydes, and hydroxyphenols for efficient and selective nuclear bromination. The hydroxy aromatics and PBC were dissolved in the minimum amount of glacial acetic acid, and the reaction mixtures were heated with constant stirring.…”
Section: N-bromophthalimidementioning
confidence: 99%
“…In 2003, Patwari et al reported this reagent as an efficient brominating agent for the bromination of hydroxy aromatics. 1183 PBC was used to brominate various substituted hydroxyacetophenones, hydroxy aldehydes, and hydroxyphenols for efficient and selective nuclear bromination. The hydroxy aromatics and PBC were dissolved in the minimum amount of glacial acetic acid, and the reaction mixtures were heated with constant stirring.…”
Section: N-bromophthalimidementioning
confidence: 99%
“…Reports on the formation of alloys, or solid solutions, of organic compounds, although still rare, have been appearing regularly in the last few years for aromatic compounds, such as substituted benzenes and naphtalenes [1][2][3], pyrene and anthracene [4][5][6], for carbohydrates [7], terpenes [8], neopentane derivatives [9-10] and fulerenes, besides solid solutions of C 60 with C 70 [11][12] solid solutions of C 60 in sulphur have been reported [13]. Nevertheless it is among the molecules with long n-alkyl chains such as n-alcohols Although the materials based on n-alkane alloys have been used for long as candles, waterproof coatings, pharmaceutical and cosmetics, and in spite of paraffin waxes being a valuable by-product of petroleum refining, the research on n-alkane solid solutions has been mainly prompted by its dark side: The damages and losses caused by wax precipitation from petroleum fluids.…”
Section: Introductionmentioning
confidence: 99%
“…Reports on the formation of alloys, or solid solutions, of organic compounds, although still rare, have been appearing regularly in the last few years for aromatic compounds, such as substituted benzenes and naphtalenes [1][2][3], pyrene and anthracene [4][5][6], for carbohydrates [7], terpenes [8], neopentane derivatives [9][10] and fulerenes, besides solid solutions of C 60 with C 70 [11][12] solid solutions of C 60 in sulphur have been reported [13]. Nevertheless it is among the molecules with long n-alkyl chains such as n-alcohols [14], fats [15], soaps [16] and alkanes [17][18][19][20] that solid solutions appear more frequently.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation